A Blue Print for a Worldwide Multimodal Regime - Alcántara González, José María; Hunt, Frazer; Johansson, Svante O.; Oland, Barry; Pysden, Kay; Pohunek, Milos; Ramberg, Jan; Schmitt, Douglas G.; Tetley, C.M., William; Vidal, Julio (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
In the issue n. 2 of 2010 of CDT it was published a manifesto of the so-called “Group of the 9” under the title of “Particular concerns with regard to the Rotterdam Rules” where these renowned scholars and attorneys expressed their doubts about this new international legal instrument. The Group offers now a new manifesto providing a step further whereby they indicate that notwithstanding the undeniable necessity to update the Hague-Visby Rules and the contributions carried out in this direction by the Rotterdam Rules, success expectations of the latter rules are hindered because of the aim to expand the scope of application beyond their object in strict sense, namely maritime transport, so as to become the text of reference as for every multimodal transport that includes a sea leg. Far from contributing to a real and effective multimodal unified regime, new doubts arise when determining which regime, of all those for each type of transport, shall apply in each case. In any event, it seems that in order to reach the objectives appointed to by the Rotterdam Rules, introducing Protocols to the Hague-Visby Rules would have been good enough, whereas all that related to multimodal transport continues by the CMR established paths, a system which should trespass European borders with the help of different international institutions.